CircACC1 Promotes NSCLC Proliferation via miR-29c-3p/MCL-1 Signaling Pathway - Zhu, Bo; Ke, Lixia; Li, Peixian; Wang, Xin; Yang, Lan; Bai, Minghua; Chen, Mailin (Frontiers in Genetics, 2022)
NSCLC remains the leading cause of cancer-related deaths worldwide with high morbidity and mortality. It is urgently needed to reveal new molecular mechanisms contribute to NSCLC progression to facilitate drug development and to improve the overall survival. Much attention had paid to the role of circRNAs in NSCLC development. However, the knowledge of circRNAs in NSCLC still limited, and need to be further explored. The dysregulation of circACC1 was evaluated by qRT-PCR in NSCLC samples and cell lines. The oncogenic role of circACC1 in NSCLC progression were analyzed by CCK8 and colony formation assays. The interaction between the circACC1 and miR-29c-3p, as well as MCL-1 was verified by qRT-PCR, western blot, the luciferase reporter assay and RIP experiment. Elevated level of circACC1 was found in NSCLC patients, and was negatively correlated with OS. Ectopic expression of circACC1 promoted the capacity of cell growth and clonogenicity, while the inhibition of circACC1 decreased the proliferation and clonogenicity potential. Mechanism studies elucidated that circACC1 contribute to cell growth via directly binding to miR-29c-3p. Transfection of miR-29c-3p mimic blocked circACC1 mediated NSCLC cell proliferation. MCL-1 is a downstream target of miR-29c-3p in NSCLC cells. The circACC1/ miR-29c-3p/ MCL-1 axis is important in NSCLS proliferation.